Reactualizing the Role of Teachers as Social Agents in the Perspective of Contemporary Sociology of Education - Siswanto, Wawan; Jauhari, Ahmad; Mulyana, Asep (Universitas Syiah Kuala, 2025)
This research aims to reactualize the role of teachers as social agents through the perspective of contemporary educational sociology. In the midst of rapid social transformation due to globalization, digitalization, and cultural pluralism, the function of teachers is no longer limited to the delivery of knowledge, but expands as actors who shape social norms, maintain community integration, and mediate structural inequality in educational institutions. Using a descriptive-qualitative method based on literature study, this paper analyzes the role of teachers in the process of reproduction and transformation of social values, negotiation of cultural identity in the classroom, and the development of students' critical awareness. This study draws on the theoretical frameworks of Emile Durkheim, Pierre Bourdieu, and Paulo Freire to explain how teachers operate within institutional structures while still having agency in driving social change. The results of the analysis show that the sociological role of teachers needs to be understood not only from an institutional point of view, but also as part of a broader socio-cultural dynamic, in which education functions as a medium of social construction. Therefore, a review of the role of teachers as social agents is important in formulating a responsive, democratic, and liberating education system.